SWService: uma biblioteca para a escrita da Língua Brasileira de Sinais baseada em Web Services - Souza, Vinicius Costa de (Universidade do Vale do Rio do Sinos, 2005)
Great advances in science have been made in the last years promoting a social-cultural changing process, in which the access to the new technologies becomes too important for all. However, most of computational tools are not prepared to people who has special necessities. Some initiatives have been developed to spread out the sign languages as a way to make possible the deaf digital and social inclusion. But, the use of these languages in software is still complex and expensive. Thus, the aim of this work was to develop a library, SWService, which provides the wanted features to enable web-based software to use the Brazilian Sign Language. This solution presents as main advantage the use of Web Services technology witch allows the SWService use without local development or installation necessity. Besides, a case study and an opinion research applied to Sign WebForum, a discussion forum which uses the SWService to permits the writing and reading of messages both in Portuguese and Libras, were realized.
Keywords: Língua Brasileira de Sinais; Sign Writing; SWService; Engenharia de software; Sign Writing; SWService; Web Services; Brazilian Sign Language; Ciências Exatas e da Terra